PENGARUH BUDAYA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA DRIVER GRAB DI KOTA PASURUAN - Kristian Idris Pamungkas Sinaga; Ratna Pudyaningsih; Yufenti Oktafiah (Jurnal Inovasi Penelitian, 2023)
Grab is one of the online transportation service providers in Pasuruan City. Drivers in Pasuruan City are accustomed to using more than one online application while working to maximize their income and continue to do this because it is based on their motivation to meet their needs. This study aims to determine the influence of work culture and work motivation on the performance of grab drivers in Pasuruan City. The population used in this study is grab drivers in Pasuruan City. The sampling technique used is using the hair et al formula, with a total of 60 responses. The data analysis techniques used in this study are descriptive analysis, classical assumption test, multiple linear regression analysis, simultaneous test (F test) and partial test (t test) and determination coefficient analysis (R2) with a significance level of 5%. The type of data in this study is primary data. The results of this study show that (1) work culture and work motivation have a positive and significant effect simultaneously on driver performance. (2) Work culture has a positive and significant effect on driver performance. (3) Work motivation has a positive and significant effect on driver performance. Work Culture and Work Motivation have an influence of 52.9% on the performance of grab drivers in Pasuruan City